Health insurance for informal workers: What is hindering uptake? Perspectives from female food vendors in Kinondoni district, Tanzania - Mushi, Lawrencia; Milanzi, Peter (East African Journal of Applied Health Monitoring and Evaluation, 2024)
Article published by the The east African Journal of Applied Health Monitoring and Evaluation Vol. 3 No. 3 (2019)